Taboo language in Deli Javanese: Realization and factors - Mhd Pujiono; Arie Azhari Nasution; Abdul Gapur; Taulia Taulia (Universitas Syiah Kuala, 2026)
This study examined the use and understanding of taboo language in Deli Javanese. It aimed to: (1) examine the manifestation of taboos in family, community, and workplace settings, and (2) identify the factors influencing their use and change over time. Using sociolinguistic and pragmatic approaches, the researchers conducted six months of participant observation and interviews with 30 native speakers across different age and gender groups. The findings showed that taboos serve as both cultural markers and social regulators. Within families, taboos reinforce hierarchy and values (e.g., fathers’ animal-based insults such as ‘kampret’ (small bat), or mothers’ moral advice such as ‘yen mangan ora usah karo ngomong’ (don’t talk while eating). In community settings, direct taboos (e.g., ‘asu’ (dog)) are used to resolve conflicts, while in workplace contexts, traditional taboos are creatively repurposed (e.g., ‘dolanan beras’ (playing with rice) to criticize inefficiency). The study revealed a generational decline in taboo knowledge: youth retain only 42% of taboo terms, favoring hybrid expressions (e.g., ‘bodoh koe!’ (you are stupid)), while elders recall up to 89%. Key influencing factors include age, gender (with men favoring solidarity and women favoring politeness), educational background, and language contact. The study concluded that, while modernization threatens traditional taboos, their adaptation in professional contexts shows resilience. It calls for documenting taboos as endangered cultural heritage and their role in language education. This research contributes to the understanding of language contact and sociolinguistic change by demonstrating how migrant communities negotiate their identity through the use of taboos.